Study on the role of primary systemic chemotherapy with anthracycline combination schedule in locally advanced breast cancer: long term follow up data - Anand, Aravindh S. (International Journal of Research in Medical Sciences, 2017)
Background: Locally advanced breast cancer (LABC) refers to a heterogeneous group of locally advanced non metastatic group of breast cancer. Primary systemic chemotherapy (PST) which forms the prime modality in LABC management has several advantages. The objective of the study was to assess the response and survival of locally advanced breast cancer patients receiving PST with Anthracycline based combination chemotherapy in Indian setting. Methods: 75 LABC patients who were treated with PST were observed and finally analyzed for survival. Chemotherapy schedules were FAC (5-Fluorouracil 500 mg/m2, Doxorubicin 50 mg/m2 and Cyclophosphamide 500 mg/m2) and FEC (5-Fluorouracil 500 mg/m2, Epirubicin 100 mg/m2 and Cyclophosphamide 500 mg/m2).Clinical complete response (cCR), partial response (PR), stable disease (SD) and pathological complete response (pCR) were assessed. 5 year overall survival (O.S) & disease free survival (DFS) were analyzed using Kaplan Meier survival analysis. Results: 94% became operable after PST and 6% remained inoperable. MRM with axillary clearance was achieved in 70.4% while simple mastectomy with axillary dissection in 22.5%. Microscopic surgical clearance achieved in 85.9%. Objective clinical tumour response rate was 78.9% with cCR of 11.3%, PR of 67.6% & pCR of 7.5%. Five year O.S and DFS were 67.92% and 62.21% respectively. Conclusions: Anthracycline based chemotherapy is an excellent schedule in neoadjuvant setting in LABC in down staging disease. But to further improve the O.S, DFS and pCR addition of agents like Taxanes and their sequencing must be explored. RCTs addressing these issues are warranted especially in countries like India.